Berkeley Saint John's - Barbra Anderson::::::photographer:::
Currently Julia Morgan Theater, College and Derby Streets, Berkeley, Julia Morgan 1872-1957, old St. John's presbyterian Church -Berkeley, credit: Barbara Anderson